Disiplin Kerja Aparatur Sipil Negara (ASN) Dalam Meningkatkan Efisiensi Kerja Pada Dinas Pendidikan Dan Kebudayaan Kabupaten Muna - Mustafa, Dian Tria Restika; Kadir, Abdul; Sartono, Sartono (Universitas Halu Oleo, 2021)
This study aims to determine how the work discipline of the State Civil Apparatus (ASN in increasing work efficiency at the Education And Culture Office in Muna Regency and to find out how the work efficiency of the State Civil Apparatus (ASN) at the Muna Regency Education and Culture Office. The method used in this research is descriptive qualitative research method, by means of observation, interviews and documentation. The results of this study indicate that Work Discipline of State Civil Apparatus (ASN) in increasing work efficiency at the Muna Regency Education and Culture Office has not been implemented properly, seen from several aspects, namely: obedience to time proved by there are still State Civil Apparatus (ASN) who are not yet on time when they come to work and come home not in time. Then in the aspect of obeying behavior at work, it is still found that the State Civil Apparatus (ASN) delegates its responsibilities to honorary employees. Meanwhile, the work efficiency of the State Civil Apparatus (ASN) is not good, which can be seen from the lack of professionalism because there is no technical training so that the State Civil Apparatus (ASN) does not understand the main duties and functions of each employee. In addition, the Muna Regency Education and Culture Office paid less attention to the matter of giving rewards or awards to the State Civil Apparatus (ASN) which aims to spur their work motivation.Â